A Critical Study of Victor Turner's Liminality, Religion, and Nationality - Wajabula, Alfred Eduard (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2023)
This paper discusses Victor Turner's theory of liminality, religion, and nationality obtained from primary sources using the literature review method. The results of his study serve as a theoretical basis for discussing Victor Turner's liminality and its relationship to religion and nationality. This theory will help the writer dissect the customary ritual of washing the land in Soya. Liminality is an important aspect of the rite and is adopted from Arnold Van Gennep's concept. The term ‘liminality’ comes from the Latin word 'limen', which means 'doorway'. Viktor Turner used this term in his research on symbols and rituals among the Ndembu people of Africa. Therefore, liminality has such rich characteristics that it provides its own perspective on the life of society and culture today. In addition to Liminality, the writer also examines the theory of religion and nationality initiated by Emile Durkheim and Ernest Gellner. The results of the study show that these three theories have a very close and substantial relationship, in which of these three theories is social equality with one another. This intersection exists as a result of Turner's theory of liminality.